Molecular sieve SSZ-91 with graded porosity, method for preparing same and use thereof
By developing SSZ-91 molecular sieve with low defect degree and low aspect ratio, the existing ZSM-48 molecular sieve has solved the problem of high hydrocracking degree and reduced selectivity during hydrocracking, and more efficient catalytic performance has been achieved.
Patent Information
- Application Number
- CN202380062885.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-01
- Filing Date
- 2023-08-01
- Publication Date
- 2025-04-18
AI Technical Summary
The existing ZSM-48 molecular sieve has a high degree of hydrocracking and reduced selectivity during the hydrocracking process, and it is difficult to obtain molecular sieves with low defect degree and pure phase.
A new class of crystalline molecular sieve SSZ-91 was developed, with low defect degree and low aspect ratio to inhibit hydrocracking and essentially pure phase characteristics. Through specific synthesis methods and conditions, SSZ-91 is structurally similar to ZSM-48, but has improved catalytic properties.
SSZ-91 significantly reduces the degree of hydrocracking and improves catalytic performance, especially in hydrotreatment applications, showing lower hydrocracking and higher selectivity.
Smart Images

Figure BDA0005290868540000081 
Figure BDA0005290868540000091 
Figure BDA0005290868540000141
Abstract
Description
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0002] This application is related to and claims priority to U.S. Provisional Application Serial No. 63 / 394,286 filed on August 1, 2022, the entirety of which is incorporated herein. Technical Field
[0003] Described herein are crystalline molecular sieves belonging to the ZSM-48 molecular sieve family, designated SSZ-91, having graded porosity, methods for preparing such SSZ-91 molecular sieves, and uses thereof. Background Art
[0004] Due to their unique screening characteristics and their catalytic performance, crystalline molecular sieves and molecular sieves are particularly useful in applications such as hydrocarbon conversion, gas drying and separation. Although many different crystalline molecular sieves have been disclosed, there is a continuous need for new molecular sieves with ideal properties for gas separation and drying, hydrocarbon and chemical conversion and other applications. The new molecular sieve can contain a novel internal pore structure to provide enhanced selectivity in these processes.
[0005] Molecular sieves have a unique crystal structure, as evidenced by their unique X-ray diffraction patterns. The crystal structure defines cavities and pores that are unique to each substance.
[0006] Molecular sieves are classified by the Structure Commission of the International Zeolite Association according to the IUPAC Commission Zeolite Nomenclature Rules. According to this classification, framework zeolites and other crystalline microporous molecular sieves whose structures have been established are assigned three-letter codes and are described in the "Atlas of Zeolite Framework Types" Sixth Revised Edition, Elsevier (2007) and in the molecular sieve structure database on the International Zeolite Association website (http: / / www.iza-online.org).
[0007] The structure of a molecular sieve can be ordered or disordered. A molecular sieve with an ordered structure has a periodic structural unit (PerBU) that is periodically ordered in three dimensions. A structure with a disordered structure exhibits periodic order in dimensions less than three dimensions (i.e., in two, one, or zero dimensions). Disorder occurs when PerBUs are connected in different ways or when two or more PerBUs coexist in the same crystal. If periodic order is achieved in all three dimensions, the crystal structure constructed by PerBUs is called an end-member structure.
[0008] In disordered materials, planar stacking defects occur when the material contains two-dimensional order. Planar defects disrupt the channels formed by the pore system of the material. Planar defects located near the surface restrict the diffusion paths that would otherwise be needed to allow feedstock components to enter the catalytically active part of the pore system. Therefore, the catalytic activity of the material generally decreases as the degree of defects increases.
[0009] In the case of crystals with planar defects, the interpretation of X-ray diffraction patterns requires the ability to simulate the effects of stacking disorder. DIFFaX is a computer program based on a mathematical model for calculating the intensity of crystals containing planar defects. See also , MMJ Treacy et al., Proceedings of the Royal Chemical Society, London, A (1991), Vol. 433, pp. 499-520). DIFFaX is a simulation program selected by and available from the International Zeolite Association for simulating XRD powder patterns of intergrown phases of molecular sieves. ( See also , "Collection of Simulated XRD Powder Patterns for Zeolites", MMJ Treacy and JB Higgins, 2001, 4th edition, published on behalf of the International Zeolite Association Structure Committee). It has also been used to theoretically study intergrown phases of AEI, CHA and KFI molecular sieves as reported by KPLillerud et al. in "Studies in Surface Science and Catalysis", 1994, Vol. 84, pp. 543-550. DIFFaX is a well-known and established method for characterizing disordered crystalline materials with planar defects, such as intergrown molecular sieves.
[0010] The name ZSM-48 refers to a class of disordered materials, each of which is characterized by having a one-dimensional 10-ring tubular pore system. These pores are formed by rolled honeycomb sheets of fused tetrahedral 6-ring structures, and the pores contain 10 tetrahedral atoms. Zeolites EU-2, ZSM-30 and EU-11 belong to the ZSM-48 zeolite family. The ZSM-48 molecular sieve family consists of nine polytypes. These materials have very similar but not identical X-ray diffraction patterns. The polytypes can be distinguished at least in part based on their morphological differences. For example, polytype 6 consists of needle-shaped crystals with a diameter of about 20 nm and a length of about 0.5 μm. Another polytype described as defect polytype 6 consists of elongated crystals with a width of about 0.5 μm and a length of 4-8 μm.
[0011] Kirschhock and co-workers describe the successful synthesis of a phase-pure polymorph of 6. (See Chem. Mater. 2009, 21, 371-380.) In their paper, Kirschhock and co-workers describe their phase-pure polymorph of 6 material (which they call COK-8) as having a morphology consisting of long needle-like crystals with a very large aspect ratio (width, 15-80 nm; length, 0.5-4 μm) that grow along the interconnected pores.
[0012] As pointed out in the Kirschhock paper, the molecular sieve from the ZSM-48 molecular sieve family consists of a 10-ring, 1-dimensional pore structure, in which the channel formed by the interconnected pores extends perpendicular to the long axis of the needle. Therefore, the channel opening is located at the short end of the needle. As the length-to-diameter ratio (also referred to as aspect ratio) of these needles increases, the diffusion path of the hydrocarbon feed also increases. As the diffusion path increases, the residence time of the feed in the channel also increases. Longer residence time leads to an increase in undesirable feed hydrocracking, while selectivity decreases.
[0013] There is a continuing need for molecular sieves in the ZSM-48 family that provide lower levels of hydrocracking and provide other improvements over known ZSM-48 molecular sieves.There is also a continuing need for molecular sieves that are phase pure or substantially phase pure and have a low degree of disorder (low degree of defects) within the structure. Summary of the invention
[0014] A class of crystalline molecular sieves having unique properties is disclosed, referred to herein as "molecular sieve SSZ-91" or simply "SSZ-91". Molecular sieve SSZ-91 is structurally similar to molecular sieves belonging to the ZSM-48 zeolite family and is characterized by: (1) having a low degree of defects, (2) a low aspect ratio that inhibits hydrocracking compared to conventional ZSM-48 materials having an aspect ratio greater than 8, and (3) being substantially phase pure. Also described herein is SSZ-91 that has been further modified to enhance pore size and pore size distribution characteristics.
[0015] A ZSM-48 material lacking any one of the three unique combined features of SSZ-91 (low aspect ratio, low EU-1 content, high polytype 6 composition) would exhibit poor catalytic performance compared to conventional ZSM-48 materials. SSZ-91 and modified SSZ-91 as further described herein exhibit improved catalytic performance, particularly in hydroprocessing applications.
[0016] In one aspect, the molecular sieve is described herein as SSZ-91 having a molar ratio of silica to alumina of from 40 to 220. The X-ray diffraction lines of Table 2 herein represent SSZ-91 in its as-made form. The SSZ-91 material consists of at least 70% polytype 6 of the total ZSM-48-type material present in the product, as determined by DIFFaX simulations and as described by Lobo and Koningsveld in J. Am. Chem. Soc. 2012, 124, 13222-13230, wherein the disorder is regulated by three different defect probabilities. It should be noted that the phrase "at least 70%" includes the case where no other ZSM-48 polytypes are present in the structure, i.e., the material is 100% pure phase polytype 6.
[0017] On the other hand, SSZ-91 is essentially phase pure.SSZ-91 contains an additional EUO-type molecular sieve phase in an amount ranging from 0 to 3.5 wt % (inclusive) of the total product.
[0018] Molecular sieve SSZ-91 has a morphology characterized by polycrystalline aggregates, each of which is characterized by being composed of crystallites having an average aspect ratio of 1-8 (including end values). SSZ-91 exhibits a lower degree of hydrocracking than those ZSM-48 materials with higher aspect ratios. An aspect ratio of 1 is the ideal minimum value, where the length and width are the same.
[0019] In additional aspects, SSZ-91 can include improved pore size and distribution characteristics, including, for example, wherein the total pore volume (measured at P / P0 of 0.95) within the mesopore diameter range (2-50 nm) is at least about 0.2 cc / g, and the micropore volume is at least 0.05 cc / g.
[0020] In another aspect, a method of preparing a mesoporous crystalline SSZ-91 material is provided by contacting (1) at least one silica source; (2) at least one alumina source; (3) at least one source of an element selected from Group 1 and Group 2 of the Periodic Table of Elements; (4) hydroxide ions; and (5) hexamethylammonium cations under conditions that result in the formation of SSZ-91, then subjecting the SSZ-91 to calcination conditions, and contacting the calcined SSZ-91 molecular sieve with an organic base, a quaternary ammonium salt, a quaternary ammonium base, an inorganic base, ammonium fluoride, or a combination thereof under solution conditions effective to desiliconize the molecular sieve; and contacting the desiliconized molecular sieve with an ammonium salt under solution conditions effective to form an ammonium-exchanged mesoporous molecular sieve. In accordance with the foregoing, the mesoporous SSZ-91 is characterized by having defined pore characteristics, such as a total pore volume (measured at a P / P0 of 0.95) within the mesopore diameter of at least about 0.2 cc / g, and wherein the micropore volume is at least 0.05 cc / g.
[0021] In another aspect, a hydroconversion process for hydroisomerizing a hydrocarbon feedstock is provided, the process comprising contacting the hydrocarbon feedstock with a hydroisomerization catalyst under hydroisomerization conditions to produce a product; wherein the hydroisomerization catalyst comprises a medium pore molecular sieve belonging to the ZSM-48 zeolite family, the molecular sieve having a total pore volume in the mesopore diameter range of at least about 0.2 cc / g (measured at a P / P0 of 0.95), and wherein the micropore volume is at least 0.05 cc / g; and wherein the molecular sieve comprises a silica to alumina molar ratio of 40-220, at least 70% polytype 6 of the total ZSM-48 type material present in the molecular sieve, and an additional EUO type molecular sieve phase in an amount of 0 to 3.5 weight percent of the total product; wherein the molecular sieve has a morphology characterized as comprising polycrystalline aggregates of crystallites collectively having an average aspect ratio of about 1 to 8. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 The nitrogen isotherm as described in Example 1 is depicted.
[0023] Figure 2 The pore size distribution (PSD) calculated from the nitrogen isotherm as described in Example 1 is depicted.
[0024] Figure 3 The nitrogen isotherm as described in Example 5 is depicted.
[0025] Figure 4 The pore size distribution (PSD) calculated from the nitrogen isotherm as described in Example 5 is depicted.
[0026] Figure 5 A nitrogen isotherm as described in Example 11 is depicted.
[0027] Figure 6 The pore size distribution (PSD) calculated from the nitrogen isotherm as described in Example 11 is depicted.
[0028] Figure 7 A nitrogen isotherm as described in Example 17 is depicted.
[0029] Figure 8 The pore size distribution (PSD) calculated from the nitrogen isotherm as described in Example 17 is depicted.
[0030] Fig. 9 A nitrogen isotherm as described in Example 20 is depicted.
[0031] Fig.10 The pore size distribution (PSD) calculated from the nitrogen isotherm as described in Example 20 is depicted. DETAILED DESCRIPTION
[0032] Although illustrative embodiments of one or more aspects are provided herein, the disclosed processes may be implemented using any number of techniques. The present disclosure is not limited to the exemplary or specific embodiments, any drawings, and any techniques (including any exemplary designs and embodiments illustrated and described herein) illustrated herein, and may be modified within the scope of the appended claims and the full scope of their equivalents.
[0033] The following description of the embodiment provides non-limiting representative examples, which refer to numbers to specifically describe the features and teachings of different aspects of the present invention. The described embodiments should be considered to be able to be implemented alone or in combination with other embodiments from the description of the embodiment. A person of ordinary skill in the art can learn and understand the different described aspects of the present invention when reading the description of the embodiment. The description of the embodiment should contribute to the understanding of the present invention, so that after reading the description of the embodiment, other implementation methods that are not specifically involved but within the scope of their ability will be understood as consistent with the application of the present invention.
[0034] Unless otherwise indicated, the following terms have the meanings as defined below.
[0035] The term "hydroconversion" refers to a process or step of hydrocracking, hydrogenation, hydrodeoxygenation, hydrodesulfurization, hydrodenitrogenation, hydrodemetallization, hydrodechlorination, hydrodecarboxylation, hydrodecarbonylation and / or hydrodearomatization of (e.g., impurities) hydrocarbon or biomass feedstocks in the presence of hydrogen, and / or hydrogenating unsaturated compounds in the feedstocks. Depending on the type of hydrocracking and reaction conditions, the products of the hydrocracking process may have, for example, increased aromatic content, oxygen content, viscosity, viscosity index, saturate content, low temperature properties, volatility, and depolarization.
[0036] The term "hydroprocessing" refers to a process or step of hydrodesulfurizing, hydrodenitrogenating, hydrodemetallizing and / or hydrodearomatizing the components (eg, impurities) of a diesel feedstock in the presence of hydrogen, and / or hydrogenating unsaturated compounds in the feedstock.
[0037] The term "active source" means a reagent or precursor material that is capable of providing at least one element in a reactive form and that can be incorporated into the molecular sieve structure. The terms "source" and "active source" are used interchangeably herein.
[0038] The terms "molecular sieve" and "zeolite" are synonymous and include (a) intermediate and (b) final or target molecular sieves as well as molecular sieves produced by (1) direct synthesis or (2) post-crystallization treatment (secondary modification). Secondary synthesis techniques allow the synthesis of target materials from intermediate materials by heteroatom lattice substitution or other techniques. For example, aluminosilicates can be synthesized from intermediate borosilicates by post-crystallization heteroatom lattice substitution of Al for B. Such techniques are known, for example, as described in U.S. Pat. No. 6,790,433, issued Sept. 14, 2004 to CY Chen and Stacey Zones.
[0039] The terms "*MRE type molecular sieve" and "EUO type molecular sieve" include all molecular sieves specified in the International Zeolite Association framework and their isotypes, as described in Atlas of Zeolite Framework Types, Ch. Baerlocher, LB McCusker and DH Olson, eds., Elsevier, 6th Revised Edition, 2007 and in the Zeolite Structure Database on the International Zeolite Association website (http: / / www.iza-online.org).
[0040] The term "Periodic Table" refers to the IUPAC Periodic Table of the Elements as of June 22, 2007, and the numbering scheme for the Periodic Table Groups is as described in Chem. Eng. News, 63(5), 26-27 (1985).
[0041] For the purpose of this specification and the appended claims, unless otherwise stated, all the numbers representing quantity, percentage or ratio and other numerical values used in the specification and claims should be understood to be modified by the term "about" in all cases. Therefore, unless otherwise indicated, the numerical parameters set forth in the following specification and the appended claims are approximate values that can be changed according to the desired properties to be sought to obtain. It should be noted that, as used in this specification and the appended claims, unless clearly and explicitly limited to an indicator, the singular forms "a kind of / one (a)", "a kind of / one (an)" and "the" include multiple indicators. As used herein, the term "include" and its grammatical variants are intended to be non-restrictive, so that the narration of the items in the list does not exclude other similar items that can be replaced or added to the listed items. As used herein, the term "include" means to include the elements or steps identified after the term, but any such element or step is not exhaustive, and the embodiment may include other elements or steps.
[0042] Unless otherwise specified, the enumeration of the types of elements, materials or other components from which a single component or a mixture of components can be selected is intended to include all possible sub-class combinations of the listed components and mixtures thereof. In addition, all numerical ranges set forth herein include their upper and lower limits.
[0043] The patentable scope is defined by the claims and may include other examples that occur to those skilled in the art. Such other examples are intended to fall within the scope of the claims if they have structural elements that do not differ from the literal language of the claims, or if they include equivalent structural elements that do not differ substantially from the literal language of the claims. All citations mentioned herein are hereby incorporated by reference herein to the extent not inconsistent herewith.
[0044] In the preparation of SSZ-91, at least one organic compound that is selective for synthesizing molecular sieves of the ZSM-48 zeolite family is used as a structure directing agent ("SDA"), which is also called a crystallization template. The SDA that can be used to prepare SSZ-91 is represented by the following structure (1):
[0045]
[0046] N,N,N,N′,N′,N′-Hexamethylhexamethylenediammonium or hexamethylammonium cation
[0047] The SDA cation is usually associated with an anion, which can be any anion that is not harmful to the formation of the molecular sieve. Representative examples of anions include hydroxide, acetate, sulfate, carboxylate and halogen, such as fluoride, chloride, bromide and iodide. In one embodiment, the anion is bromide.
[0048] Generally, SSZ-91 is prepared by the following steps: (a) preparing a reaction mixture comprising (1) at least one silica source; (2) at least one alumina source; (3) at least one source of an element selected from Group 1 and Group 2 of the periodic table; (4) hydroxide ions; (5) hexamethylammonium cations; and (6) water; and (b) maintaining the reaction mixture under crystallization conditions sufficient to form crystals of the molecular sieve.
[0049] The composition of the reaction mixture for forming the molecular sieve expressed in molar ratio is shown in Table 1 below:
[0050] Table 1
[0051]
[0052] in,
[0053] (1) M is selected from the group consisting of elements from Group 1 and Group 2 of the Periodic Table of Elements; and
[0054] (2) Q is a structure directing agent represented by the above structure 1.
[0055] Silicon sources useful herein include fumed silica, precipitated silica, silica hydrogel, silicic acid, colloidal silica, tetraalkyl orthosilicates (eg, tetraethyl orthosilicate), and silica hydroxide.
[0056] Aluminum sources useful herein include aluminates, alumina, and aluminum compounds such as AlCl3, Al2(SO4)3, Al(OH)3, kaolin and other zeolites. An example of an alumina source is LZ-210 zeolite (a Y-type zeolite).
[0057] As described above, for each embodiment described herein, a reaction mixture comprising at least one source of an element selected from Group 1 and Group 2 of the periodic table (referred to herein as M) can be formed. In one sub-embodiment, a source of an element from Group 1 of the periodic table is used to form the reaction mixture. In another sub-embodiment, a sodium (Na) source is used to form the reaction mixture. Any M-containing compound that is harmless to the crystallization process is suitable. Sources of such Group 1 and Group 2 elements include oxides, hydroxides, nitrates, sulfates, halides, oxalates, citrates, and acetates thereof.
[0058] For each embodiment described herein, the molecular sieve reaction mixture can be supplied by more than one source. In addition, two or more reaction components can be provided by one source.
[0059] The reaction mixture may be prepared batchwise or continuously.The crystal size, morphology and crystallization time of the molecular sieves described herein may vary depending on the nature of the reaction mixture and the crystallization conditions.
[0060] The reaction mixture is maintained at an elevated temperature until crystals of the molecular sieve are formed. In general, the hydrothermal crystallization of zeolites is usually carried out under pressure, and is usually carried out in an autoclave, so that the reaction mixture is subjected to autogenous pressure and optional stirring at a temperature of 125° C. to 200° C. for a period of 1 to 18 hours or more.
[0061] As described above in this article, SSZ-91 is a substantially pure phase material. As used herein, the term "substantially pure phase material" means that the material is completely free of zeolite phases other than zeolite phases belonging to the ZSM-48 zeolite family, or the amount of its presence has an insufficiently measurable effect on the selectivity of the material, or is insufficient to cause a material disadvantage in the selectivity of the material. Two common phases co-crystallized with SSZ-91 are EUO-type molecular sieves, such as EU-1, as well as Magadiite and Kenyaite. These additional phases may exist as separate phases, or may coexist with SSZ-91 phases. As shown in the following examples, the presence of a large amount of EU-1 in the product is detrimental to the selectivity of SSZ-91 hydroisomerization.
[0062] In one embodiment, the SSZ-91 product contains an additional EUO-type molecular sieve phase in an amount of 0 to 3.5 wt%. In a sub-embodiment, the SSZ-91 contains 0.1 to 2 wt% EU-1. In another sub-embodiment, the SSZ-91 contains 0.1 to 1 wt% EU-1.
[0063] It is known that the ratio of the powder XRD peak intensity varies linearly as a function of the weight fraction of any two phases in a mixture: (Iα / Iβ)=(RIRα / RIRβ)*(xα / xβ), where the RIR (reference intensity ratio) parameter can be found in the Powder Diffraction File (PDF) database of the International Diffraction Data Center (http: / / www.icdd.com / products / ). Therefore, the weight percentage of the EUO phase is calculated by measuring the ratio between the peak intensity of the EUO phase and the peak intensity of the SSZ-91 phase.
[0064] The amount of EUO phase formed is suppressed by selecting the optimal hydrogel composition, temperature, and crystallization time that minimizes the formation of the EUO phase while maximizing the yield of the SSZ-91 product. The following examples provide guidance on how changes in these process variables can minimize the formation of EU-1. A zeolite manufacturer with ordinary skill in the art will be able to readily select the process variables required to minimize the formation of EU-1, as these variables will depend on the scale of the production run, the capacity of the available equipment, the desired target yield, and the acceptable level of EU-1 material in the product.
[0065] During the hydrothermal crystallization step, molecular sieve crystals may be allowed to spontaneously nucleate from the reaction mixture. The use of molecular sieve crystals as seed materials may be advantageous in reducing the time required for complete crystallization to occur. In addition, seed crystals may lead to an increase in the purity of the product obtained by promoting nucleation and / or formation of the molecular sieve on any undesirable phase. However, it has been found that if seed crystals are employed, the seed crystals must be very phase-pure SSZ-91 to avoid the formation of a large amount of EUO phase. When used as seed crystals, the amount of seed crystals added is between 0.5% and 5% of the weight of the silicon source used in the reaction mixture.
[0066] Because Magadiite and Kenyaite are layered sodium silicate compositions, the formation of Magadiite and Kenyaite is minimized by optimizing the hexamethylammonium bromide / SiO2 ratio, controlling the hydroxide concentration, and minimizing the sodium concentration.
[0067] Once the molecular sieve crystals are formed, the solid product is separated from the reaction mixture by standard mechanical separation techniques (such as filtration). The crystals are washed with deionized water and then dried to obtain the original synthesized molecular sieve crystals. The drying step can be carried out under atmospheric pressure or vacuum.
[0068] The molecular sieve can be used in the state of as-synthesis, but is usually heat-treated (calcined). The term "as-synthesized" refers to the molecular sieve in the form after crystallization and before the removal of the SDA cation. SDA can be removed by heat treatment (e.g., calcination), preferably in an oxidizing atmosphere (e.g., air, a gas with an oxygen partial pressure greater than 0 kPa) at a temperature that can be easily determined by those skilled in the art to be sufficient to remove SDA from the molecular sieve. SDA can also be removed by ozonation and photolysis techniques as described in U.S. Patent No. 6,960,327 (e.g., exposing the molecular sieve product containing SDA to light or electromagnetic radiation with a wavelength shorter than visible light under conditions sufficient to selectively remove organic compounds from the molecular sieve).
[0069] The molecular sieve may then be calcined in steam, air or an inert gas at a temperature in the range of 200°C to 800°C for a period of time in the range of 1 to 48 hours or longer. Typically, it is desirable to remove extra-framework cations (e.g., Na + ) and replace it with hydrogen, ammonium or any desired metal ion.
[0070] When the molecular sieve formed is an intermediate molecular sieve, the target molecular sieve can be achieved using post-synthesis techniques (such as heteroatom lattice substitution techniques). The target molecular sieve (e.g., silicate SSZ-91) can also be obtained by removing heteroatoms from the lattice by known techniques (such as acid leaching).
[0071] The molecular sieve manufactured by the method disclosed herein can form a variety of physical shapes. Generally speaking, the molecular sieve can be in the form of a powder, granule or molded product, such as having an extrudate that is enough to pass through 2 mesh (Tyler) screens and remain on a particle size on a 400 mesh (Tyler) screen. In the case where the catalyst is molded (such as by extruding with an organic binder), the molecular sieve can be extruded before drying, or dried or partially dried and then extruded.
[0072] Molecular sieves can be compounded with other materials that are tolerant to the temperature and other conditions used in organic conversion processes. Such matrix materials include active and inactive materials and synthetic or naturally occurring molecular sieves and inorganic materials such as clays, silica and metal oxides. Examples of such materials and the manner in which they can be used are disclosed in U.S. Patent Nos. 4,910,006 and 5,316,753.
[0073] The extrudate or particles can then be further loaded with one or more active metals selected from the group consisting of Group 8 to 10 metals of the periodic table using techniques such as impregnation or ion exchange to enhance hydrogenation functionality. It may be desirable to co-impregnate the modifying metal and one or more Group 8 to 10 metals simultaneously, as disclosed in U.S. Pat. No. 4,094,821. In one embodiment, at least one active metal is selected from the group consisting of nickel, platinum, palladium, and combinations thereof. After loading the metal, the metal-loaded extrudate or particles can be calcined in air or an inert gas at a temperature of 200° C. to 500° C. In one embodiment, the metal-loaded extrudate is calcined in air or an inert gas at a temperature of 390° C. to 482° C.
[0074] SSZ-91 can be used in various hydrocarbon conversion reactions, such as hydrocracking, dewaxing, olefin isomerization, alkylation, and isomerization of aromatic compounds, etc. SSZ-91 can also be used as an adsorbent for general separation purposes.
[0075] The SSZ-91 molecular sieve prepared by the method disclosed herein has a SiO2 / Al2O3 molar ratio (SAR) of 40 to 200. SAR is determined by inductively coupled plasma (ICP) elemental analysis. In one sub-embodiment, SSZ-91 has a SAR of 70 to 160. In another sub-embodiment, SSZ-91 has a SAR of 80 to 140.
[0076] The SSZ-91 material consists of at least 70% polytype 6 of the total ZSM-48-type material present in the product, as determined by DIFFaX simulations and as described by Lobo and Koningsveld in J. Am. Chem. Soc. 2012, 124, 13222-13230, where disorder is regulated by three different defect probabilities. It should be noted that the phrase "at least X%" includes the case where no other ZSM-48 polytypes are present in the structure, i.e., the material is 100% polytype 6. The structure of polytype 6 is as described by Lobo and Koningsveld ( See, J. Am. Chem. Soc. 2002, 124, 13222-13230). In one embodiment, the SSZ-91 material consists of at least 80% polytype 6 of the total ZSM-48-type material present in the product. In another embodiment, the SSZ-91 material consists of at least 90% polytype 6 of the total ZSM-48-type material present in the product. The polytype 6 structure has been given the framework code *MRE by the Structure Committee of the International Zeolite Association.
[0077] Molecular sieve SSZ-91 has a morphology characterized by having a polycrystalline aggregate with a diameter of about 100nm to 1.5μm, each polycrystalline aggregate containing a collection of crystallites having an average aspect ratio of 1 to 8. As used herein, the term "diameter" refers to the shortest length of the short end of each crystallite detected. SSZ-91 exhibits a lower degree of hydrocracking than those ZSM-48 materials with a higher aspect ratio. In one sub-embodiment, the average aspect ratio is 1 to 5. In another sub-embodiment, the average aspect ratio is 1 to 4. In yet another sub-embodiment, the average aspect ratio is 1 to 3.
[0078] Molecular sieves synthesized by the methods disclosed herein can be characterized by their XRD patterns. The powder XRD lines in Table 2 represent the original synthesized SSZ-91 prepared according to the method described in US 9,802,830. Slight changes in the diffraction pattern may be caused by changes in the molar ratio of the framework material of a particular sample due to changes in the lattice constant. In addition, sufficiently small crystals will affect the shape and intensity of the peaks, resulting in significant broadening of the peaks. Slight changes in the diffraction pattern may also be caused by changes in the organic compounds used in the preparation and changes in the Si / Al molar ratio between samples. Calcination may also result in slight changes in the XRD pattern. Despite these slight disturbances, the basic lattice structure remains unchanged.
[0079] Table 2 Characteristic peaks of the original synthesized SSZ-91
[0080]
[0081] (a) ±0.20
[0082] (b) The powder XRD patterns provided are based on a relative intensity scale, where the most intense line in the X-ray pattern is assigned a value of 100: W = weak (>0 to ≤20); M = moderate (>20 to ≤40); S = strong (>40 to ≤60); VS = very strong (>60 to ≤100).
[0083] The X-ray diffraction patterns in Table 3 are representative of calcined SSZ-91 prepared according to the methods described herein.
[0084] Table 3 Characteristic peaks of calcined SSZ-91
[0085]
[0086]
[0087] (a) ±0.20
[0088] (b) The powder XRD patterns provided are based on a relative intensity scale, where the most intense line in the X-ray pattern is assigned a value of 100: W = weak (>0 to ≤20); M = moderate (>20 to ≤40); S = strong (>40 to ≤60); VS = very strong (>60 to ≤100).
[0089] The powder X-ray diffraction patterns presented herein were collected by standard techniques. The radiation is CuK α The peak height and position (as a function of 2θ, where θ is the Bragg angle) are read from the relative intensity of the peak (adjusted for the background), and the interplanar spacing d corresponding to the recorded line can be calculated.
[0090] SSZ-91 can be further modified to introduce mesoporosity, in particular to provide mesoporosity that enhances the performance of catalysts made from mesoporous SSZ-91. As is generally known in the art, the creation of mesopores in zeolite crystals increases the accessible surface area of the catalyst and allows reactants and products to diffuse more rapidly. These mesopores are often referred to as hierarchical pores and can generally be created by two methods: 1) a "top-down" strategy, in which hierarchical pores are created in zeolite crystals after synthesis, or 2) a "bottom-up" strategy, in which hierarchical pores are created during synthesis. Although such methods are commonly used for other zeolites, there are challenges due to unpredictable behavior in achieving economically viable catalytic performance improvements.
[0091] Nevertheless, certain methods have been found to be effective in introducing mesoporosity into SSZ-91 such that catalysts prepared therefrom provide enhanced catalytic performance. According to the present invention, a mesoporous molecular sieve belonging to the ZSM-48 zeolite family, such as mesoporous SSZ-91, having a total pore volume of at least about 0.2 cc / g (measured at P / P0 of 0.95) in the mesopore diameter range (2-50 nm) and wherein the micropore volume is at least 0.05 cc / g, can be prepared by a method comprising preparing a reaction mixture comprising at least one silicon source, at least one aluminum source, at least one source of an element selected from Groups 1 and 2 of the periodic table, hydroxide ions, hexamethylammonium cations, and water; and subjecting the reaction mixture to crystallization conditions sufficient to form crystals of the molecular sieve; subjecting the molecular sieve to calcination conditions sufficient to form a calcined molecular sieve; contacting the calcined molecular sieve with an organic base, a quaternary ammonium salt, a quaternary ammonium base, an inorganic base, ammonium fluoride, or a combination thereof under solution conditions effective to desiliconize the molecular sieve; and contacting the desiliconized molecular sieve with an ammonium salt under solution conditions effective to form an ammonium-exchanged mesoporous molecular sieve.
[0092] Generally speaking, suitable calcination conditions include heating the molecular sieve to a temperature in the range of 80 to 140°C for a period of 60 to 200 min; and a) heating the molecular sieve to a temperature in the range of 450 to 550°C for a period of 60 to 300 min, or b) heating the molecular sieve to a temperature in the range of 560 to 600°C for a period of 60 to 300 min; or a combination thereof. The calcination conditions may include one or all of the aforementioned conditions, for example, heating the molecular sieve to a temperature in the range of 80 to 140°C for a period of 60 to 200 min; heating the molecular sieve to a temperature in the range of 450 to 550°C for a period of 60 to 300 min; and heating the molecular sieve to a temperature in the range of 560 to 600°C for a period of 60 to 300 min.
[0093] Mesoporous SSZ-91 can be made directly from SSZ-91 by contacting a calcined SSZ-91 molecular sieve with an organic base, a quaternary ammonium salt, a quaternary ammonium base, an inorganic base, ammonium fluoride or a combination thereof under solution conditions effective to desiliconize the molecular sieve; and contacting the desiliconized molecular sieve with an ammonium salt under solution conditions effective to form an ammonium-exchanged mesoporous molecular sieve. Although suitable mesoporous SSZ-91 molecular sieves according to the present invention have a total pore volume of at least about 0.2 cc / g (measured at P / P0 of 0.95) within the mesopore diameter range (2-50 nm), and wherein the micropore volume is at least 0.05 cc / g, the aforementioned method can also be used to produce mesoporous SSZ-91 (or other ZSM-48 zeolites) having different pore volume characteristics.
[0094] In the aforementioned method, the ammonium salt may include, for example, an ammonium halide, such as ammonium chloride or ammonium fluoride, ammonium acetate, ammonium nitrate or ammonium sulfate. The concentration of the ammonium salt (e.g., ammonium fluoride) may generally be in the range of 0.01-80% by weight, or in the range of 1-60% by weight, or in the range of 10-50% by weight.
[0095] Although not limited thereto, the organic base may be, for example, ammonia, amines, including those having the general formula R 3-n NH n (wherein R is an alkyl group and n is 0 to 2) monoalkylamines, dialkylamines and trialkylamines, such as methylamine, dimethylamine, trimethylamine, etc., and / or ammonium compounds, such as alkylammonium compounds, including those having the general formula [R 4-n NH n ] + (wherein R is an alkyl group and n is 1 to 3), and combinations thereof. Representative ammonium cations include, for example, tetraalkylammonium compounds such as tetramethylammonium, tetraethylammonium, tetrapropylammonium, and the like, and trialkyl and tetraalkylammonium compounds containing long chain alkyl groups, for example, hexadecyltrialkylammonium compounds such as hexadecyltrimethylammonium. Ammonium counter anions include halides such as F - , Cl - Br - and I - or other anions such as OH - PF 6- , BF 4-- 、CH3COO - 、SO4 - ,RCOO - (wherein R is an alkyl group), etc., and combinations thereof. The concentration of the organic base may generally be in the range of 0.001-5 mol / L, or in the range of 0.01-2 mol / L, or in the range of 0.02-1.0 mol / L.
[0096] Suitable inorganic bases include, for example, hydroxides with suitable metal cations such as sodium, potassium, lithium, etc. and / or with other cations such as ammonium, and combinations thereof. The concentration of the inorganic base can be generally in the range of 0.001-5 mol / liter, or in the range of 0.01-2 mol / liter, or in the range of 0.02-1.0 mol / liter.
[0097] Suitable quaternary ammonium salts include, for example, ammonium compounds such as alkylammonium compounds, including compounds having the general formula [R 4- n NH n ] +(wherein R is an alkyl group and n is 1 to 3), and combinations thereof. Representative ammonium cations include, for example, tetraalkylammonium compounds such as tetramethylammonium, tetraethylammonium, tetrapropylammonium, and the like, and trialkyl and tetraalkylammonium compounds containing long chain alkyl groups, for example, hexadecyltrialkylammonium compounds such as hexadecyltrimethylammonium. Ammonium counter anions include halides such as F - , Cl - Br - and I - or other anions such as OH - PF 6- , BF 4-- 、CH3COO - 、SO4 - ,RCOO - (wherein R is an alkyl group), etc., and combinations thereof. The concentration of the quaternary ammonium salt may generally be in the range of 0.001-5 mol / L, or in the range of 0.01-2 mol / L, or in the range of 0.02-1.0 mol / L.
[0098] Suitable quaternary ammonium bases include, for example, ammonium compounds containing a hydroxide anion, such as alkylammonium hydroxide compounds, including compounds containing compounds having the general formula [R 4-n NH n ] + (wherein R is an alkyl group and n is 1 to 3), and combinations thereof. Representative ammonium cations include, for example, tetraalkylammonium compounds such as tetramethylammonium, tetraethylammonium, tetrapropylammonium, and the like, and trialkyl and tetraalkylammonium compounds containing long chain alkyl groups, for example, hexadecyltrialkylammonium compounds such as hexadecyltrimethylammonium. In addition to hydroxide anions, suitable ammonium counter anions also include halides such as F - , Cl - Br - and I - , or other anions such as PF 6- , BF 4-- 、CH3COO - 、SO4 - ,RCOO - (wherein R is an alkyl group), etc., and combinations thereof. The concentration of the quaternary ammonium base may generally be in the range of 0.001-5 mol / L, or in the range of 0.01-2 mol / L, or in the range of 0.02-1.0 mol / L.
[0099] Although not limited thereto, typically, the ratio of molecular sieve to solution (wt / wt) is in the range of 0.001-1.0, or in the range of 0.005-0.2, or in the range of 0.01-0.1. Similarly, the hydroxide (OH) provided by the inorganic base- ) to molecular sieve ratio is usually 2.5x10 -4 Up to 1.0x10 -2 mol OH - / g-molecular sieve range, or within 2.5x10 -4 Up to 5.0x10 -3 mol OH - / g-molecular sieve range, or within 2.5x10 -4 Up to 3.0x10 -3 mol OH - / g-molecular sieve range.
[0100] Suitable process conditions include, but are not limited to, a solution temperature typically in the range of 1-95°C, or in the range of 5-95°C, or in the range of ambient temperature to 95°C, or wherein the solution temperature is up to the boiling point of the solution; a desiliconization temperature typically in the range of 1-95°C, or in the range of 5-95°C, or in the range of ambient temperature to 95°C. Agitation of the solution is typically performed by, for example, stirring, tumbling, ultrasound, or a combination thereof. Separation and recovery of the mesoporous molecular sieve can be performed by any effective means, for example, by filtration, centrifugation, sedimentation, or a combination thereof.
[0101] The X-ray diffraction patterns in Table 4 are representative of calcined mesoporous SSZ-91 prepared according to the methods described herein.
[0102] Table 4
[0103] Characteristic peaks of mesoporous SSZ-91
[0104]
[0105] (a) ±0.20
[0106] (b) The powder XRD patterns provided are based on a relative intensity scale, where the most intense line in the X-ray pattern is assigned a value of 100: W = weak (>0 to ≤20); M = moderate (>20 to ≤40); S = strong (>40 to ≤60); VS = very strong (>60 to ≤100).
[0107] The catalyst can be formed from mesoporous SSZ-91 (or other mesoporous ZSM-48 zeolites according to the present invention) by any technique known in the art. Suitable catalysts are loaded with one or more metals from Groups 7 to 10 and 14 of the Periodic Table of Elements, including, for example, platinum and / or palladium or other precious metals and / or base metals.
[0108] The mesoporous SSZ-91 (or other mesoporous ZSM-48 zeolites according to the present invention) typically has a silica to alumina molar ratio of 40 to 220, at least 70% polytype 6 of the total ZSM-48 type material present in the molecular sieve, and an additional EUO type molecular sieve phase in an amount of 0 to 3.5 weight % of the molecular sieve; wherein the molecular sieve has a morphology characterized by comprising polycrystalline aggregates of crystallites having a common average aspect ratio of about 1 to 8; and wherein the molecular sieve has a total pore volume (measured at P / P0 of 0.95) of at least about 0.2 cc / g within the mesoporous material diameter range (2-50 nm), and wherein the micropore volume is at least 0.05 cc / g. In some cases, the medium pore SSZ-91 molecular sieve (or other medium pore ZSM-48 zeolites according to the present invention) can have a pore volume of at least about 0.2 to 0.6 cc / g, or about 0.22 to 0.55 cc / g, or about 0.22 to 0.0.50 cc / g in the medium pore diameter range when P / P0 is 0.95. In some cases, the medium pore SSZ-91 molecular sieve (or other medium pore ZSM-48 zeolites according to the present invention) can have a total pore volume of at least about 0.25 cc / g, or in the range of about 0.25 to 0.8 cc / g, or in the range of about 0.28 to 0.65 cc / g, or in the range of about 0.28 to 0.60 cc / g when P / P0 is 0.95. In some cases, the medium pore SSZ-91 molecular sieve (or other medium pore ZSM-48 zeolites according to the present invention) can have a micropore volume in the range of about 0.05 to 0.100 cc / g, or in the range of about 0.05 to 0.090 cc / g, or in the range of about 0.05 to 0.085 cc / g. In some cases, the medium pore SSZ-91 molecular sieve (or other medium pore ZSM-48 zeolites according to the present invention) can have a micropore volume of at least about 275 m / g. 2 / g, or about 275 to 500m 2 / g, or in the range of about 275 to 450 m 2 / g, or about 275 to 400 m 2 In some cases, the mesoporous SSZ-91 molecular sieve (or other mesoporous ZSM-48 zeolites according to the present invention) may have a Bronsted acidity ( ) of at least about 175 mmol / g, or in the range of about 175 to 500 mmol / g, or in the range of about 175 to 400 mmol / g, or in the range of about 175 to 300 mmol / g. In some cases, the medium pore SSZ-91 molecular sieve (or other medium pore ZSM-48 zeolites according to the present invention) can have a silica to alumina ratio (SAR) in the range of about 40-200, or in the range of about 40-150, or in the range of about 40-120, or in the range of about 50-200, or in the range of about 50-150, or in the range of about 50-120.
[0109] The medium pore SSZ-91 (or other medium pore ZSM-48 zeolites according to the present invention) provides favorable hydroconversion capabilities. In one aspect, a hydroconversion process useful for hydroisomerizing a hydrocarbon feedstock can be carried out using a catalyst comprising a mesoporous molecular sieve, for example by contacting the hydrocarbon feedstock with a hydroisomerization catalyst under hydroisomerization conditions to produce a product; wherein the hydroisomerization catalyst comprises a mesoporous molecular sieve belonging to the ZSM-48 zeolite family, the molecular sieve having a total pore volume (measured at a P / P0 of 0.95) of at least about 0.2 cc / g within the mesoporous material diameter range (2-50 nm), and wherein the micropore volume is at least 0.05 cc / g; and wherein the molecular sieve comprises a silica to alumina molar ratio of 40-220, at least 70% polytype 6 of the total ZSM-48 type material present in the molecular sieve, and an additional EUO type molecular sieve phase in an amount of 0-3.5 weight % of the total product; wherein the molecular sieve has a morphology characterized as comprising polycrystalline aggregates of crystallites collectively having an average aspect ratio of about 1 to 8. Suitable catalysts according to the foregoing include mesoporous zeolites and metals selected from the 7th to 10th and 14th metals of the periodic table, such as Pt, Pd or combinations thereof, or other precious metals and / or base metals. Although not limited thereto, the metal content is typically 0.01-5.0 wt % or 0.01-2.0 wt % or 0.1-2.0 wt % (based on total catalyst weight). Mesoporous materials can be combined with other molecular sieves, for example, as catalysts. Other substrates or carrier materials may also be included, including materials such as aluminum oxide, silicon dioxide, titanium dioxide or combinations thereof. Generally speaking, the catalyst may include 0.01 to 5.0 wt % of metal, 1 to 80 wt % of substrate / carrier material and 0.1 to 99 wt % of molecular sieves.
[0110] The hydroconversion process can utilize many conventional petroleum feedstocks and / or biogenic feedstocks, including, for example, gas oils; vacuum gas oils; long residue; vacuum residue; atmospheric distillates; heavy fuels; oils; waxes and paraffins; used oils; deasphalted residues or crude oils; charges resulting from thermal or catalytic conversion processes; shale oils; cycle oils; fats, oils and waxes of animal and vegetable origin; petroleum and slack waxes; or combinations thereof.
[0111] Generally speaking, medium pore molecular sieves can be used to prepare catalysts that provide favorable catalytic performance benefits. For example, in some cases, catalysts according to the present invention provide catalysts having a selectivity of 90% or more, a catalyst activity temperature of 585°F or less measured at 96% conversion, or 0.9% or less as a percentage of the C produced. 4- The light fraction yield measured as a cracking product, or a combination thereof, is a hydrocarbon product of hydroisomerization. In some cases, the selectivity is 90% or more and the catalyst activity temperature is 585°F or less, or the selectivity is 90% or more and the C 4- The light fraction yield measured in the cracked products is 0.9% or less, or the catalyst activity temperature is 585°F or less and the C 4- The light fraction yield measured as cracked products is 0.9% or less, or a combination thereof. In some cases, the selectivity is 90% or more, the catalyst activity temperature is 585°F or less, and the C 4- The light fraction yield measured in cracked products is 0.9% or less. In some cases, the selectivity is equal to or greater than 91% or 92%, or wherein the catalyst activity temperature is equal to or less than 582°F, or 580°F, or 575°F, or 570°F, or wherein C 4- The light fraction yield of the cracked product is equal to or less than 0.85%, or 0.8%, or 0.7%, or 0.6%, or 0.5%, or 0.4%, or 0.3%, or 0.2%, or a combination thereof.
[0112] Example
[0113] Examples 1-40 demonstrate that catalysts comprising a mesoporous ZSM-48 material having the three unique combined features of SSZ-91 (low aspect ratio, low EU-1 content, high polytype 6 composition) and having mesoporosity as described and exemplified herein exhibit improved catalytic performance. The following illustrative examples are intended to be non-limiting.
[0114] The dried product was subjected to micropore volume analysis using N2 as the adsorbate and the micropore volume was determined via the t-plot method to provide the micropore volume in cm 3 / g is the micropore volume. See, for example, Lippens, Bo C. and JH De Boer. "Studies on pore systems in catalysts: V. The t method." Journal of Catalysis 4, No. 3 (1965): 319-323.
[0115] The total pore volume is determined based on the amount of inert gas adsorbed at a relative pressure of 0.95 (P / P0=0.95) via the Gurvich rule. See, for example, Thommes, Matthias et al. "Physisorption of gases, with special reference to the evaluation of surface area and pore size distribution (IUPAC Technical Report). "Pure and applied chemistry 87.9-10 (2015): 1051-1069.
[0116] The BET surface area is determined according to known procedures. See, for example, Thommes, Matthias et al. "Physisorption of gases, with special reference to the evaluation of surface area and pore size distribution (IUPAC Technical Report). "Pure and applied chemistry 87.9-10 (2015): 1051-1069.
[0117] The Bronsted acid site density was determined by temperature-programmed desorption of n-propylamine. See, for example, Farneth, WE and RJ Gorte. "Methods for characterizing zeolite acidity." Chemical reviews 95, No. 3 (1995): 615-635; WO 2016 / 069073A1.
[0118] The silica to alumina (SAR) molar ratio was determined by inductively coupled plasma spectroscopy according to known techniques.
[0119] Example 1 - Comparative Evaluation of SSZ-91
[0120] A sample of zeolite SSZ-91 in ammonium form was prepared according to U.S. Patent No. 9,802,830. The material was calcined in air by placing a thin bed in a calcining dish and heating in a muffle furnace from room temperature to 120°C at a rate of 1°C / min and holding for 2 hours. The temperature was then raised to 540°C at a rate of 1°C / min and held for 5 hours. The temperature was again raised to 595°C at 1°C / min and held for 5 hours. The material was then allowed to cool to room temperature.
[0121] The material is then converted to the ammonium form by heating in an ammonium nitrate solution (typically 1 g NH4NO3 / 1 g zeolite in 10 mL H2O at 95°C for at least 3 hours). The material is then filtered. This is repeated twice for a total of 3 exchanges. Finally, the material is washed with deionized (DI) water until the conductivity of the water is less than 50 μS / cm.
[0122] The analysis of nitrogen isotherms showed that the micropore volume of the t-diagram method was 0.067cc / g and the surface area of the t-diagram method was 99m 2 / g, and a BET surface area of 245m 2 The total pore volume was measured at P / P0=0.95 and found to be 0.26. The molar ratio of silica to alumina was found to be 116.
[0123] The nitrogen isotherm is shown in Figure 1 and the pore size distribution (PSD) calculated from the nitrogen isotherm is shown in Figure 2 In. PSD is calculated by density functional theory (DFT), which is a well-known method for calculating PSD in the art. As a non-limiting reference, see Landers, John, Gennady Yu Gor, and Alexander V. Neimark. "Density functional theory methods for characterization of porous materials." Colloids and Surfaces A: Physicochemical and Engineering Aspects 437 (2013): 3-32 and Kupgan, Grit, Thilanga P. Liyana-Arachchi, and Coray M. Colina. "NLDFT pore size distribution in amorphous microporous materials." Langmuir 33, No. 42 (2017): 11138-11145 for more details. Figure 1 The shape of the nitrogen isotherm shown is typical for microporous materials, and the sharp increase in volume near P / P0=1 is due to intracrystalline condensation. Figure 2 The mesopore size distribution shown also does not indicate any significant mesoporosity.
[0124] The material is then converted to the ammonium form by heating in an ammonium nitrate solution (typically 1 g NH4NO3 / 1 g zeolite in 10 mL H2O at 95°C for at least 3 hours). The material is then filtered. This is repeated twice for a total of 3 exchanges. Finally, the material is washed with DI water until the conductivity of the water is less than 50 μS / cm.
[0125] The analysis of nitrogen isotherms showed that the micropore volume of the t-diagram method was 0.067cc / g and the surface area of the t-diagram method was 112m 2 / g, and a BET surface area of 260 m 2 The total pore volume was measured at P / P0=0.95 and found to be 0.26. The found value of the silica to alumina molar ratio was 114.
[0126] The ammonium exchanged samples were subjected to palladium ion exchange using tetraammine palladium (II) nitrate (0.5 wt % Pd). After ion exchange, the samples were dried at 95°C and then calcined in air at 482°C for 3 hours to convert the tetraammine palladium (II) nitrate into palladium oxide. Finally, the material was granulated, crushed and sieved to 20-40 mesh.
[0127] Example 2 - Preparation of Mesoporous SSZ-91
[0128] A solution of 100 mL of 0.12 M NaOH and 0.08 M tetrapropylammonium bromide was prepared and heated to 75° C. 4 g of SSZ-91 in ammonium form from Example 1 was then added and the solution was stirred at 75° C. for 60 minutes. The solid was collected by filtration and washed thoroughly with DI water until the conductivity was less than 50 μS / cm, then dried in air at 95° C. The material was converted to the ammonium form by heating in an ammonium nitrate solution (typically 1 g NH4NO3 / 1 g zeolite was heated in 10 mL H2O at 95° C. for at least 3 hours). The material was then filtered. This was repeated twice for a total of 3 exchanges. Finally, the material was washed with DI water until the conductivity of the water was less than 50 μS / cm. The yield based on the weight of the recovered solid was 59%.
[0129] The analysis of nitrogen isotherms showed that the micropore volume of the t-diagram method was 0.030cc / g and the surface area of the t-diagram method was 141m 2 / g, and a BET surface area of 211m 2 / g. The total pore volume was measured at P / P0 = 0.95, and the measured value was 0.51 cc / g. The mesopore diameter determined by PSD was calculated as The Bronsted acid site density was determined by temperature-programmed desorption of n-propylamine and was found to be 166 μmol H + / g.
[0130] Analysis of the nitrogen isotherms and the PSD calculated from the nitrogen isotherms showed that the material had only small changes in micropore volume and surface area, but a significant increase in total pore volume, indicating the formation of mesopores. This is consistent with the nitrogen PSD, which indicates the presence of mesopores.
[0131] Following the procedure in Example 1, the palladium exchanged material contained 0.5 wt% Pd.
[0132] Example 3
[0133] A sample of zeolite SSZ-91 in the ammonium form was prepared according to Example 1.
[0134] The analysis of nitrogen isotherms showed that the micropore volume of the t-diagram method was 0.071cc / g and the surface area of the t-diagram method was 85m 2 / g, and a BET surface area of 240 m 2 / g. The total pore volume was measured at P / P0 = 0.95 and found to be 0.23. The molar ratio of silica to alumina was found to be 121. The Bronsted acid site density determined by programmed temperature desorption of n-propylamine was found to be 185 μmol H + / g.
[0135] Example 4
[0136] A 0.1 M NaOH solution was heated to 50° C., then 5 g of SSZ-91 from Example 3 (50 mL / g-zeolite) was added and stirred at 50° C. for 60 min. The solid was collected by filtration and washed thoroughly with DI water to a conductivity of less than 50 μS / cm, then dried in air at 95° C. The material was then converted to the ammonium form following the procedure given in Example 1.
[0137] The yield based on the recovered solids was 79%. Analysis of the nitrogen isotherm showed a t-map micropore volume of 0.063 cc / g and a t-map external surface area of 166 m 2 / g, and a BET surface area of 305m 2 / g. The total pore volume was measured at P / P0 = 0.95 and was found to be 0.40 cc / g. The molar ratio of silica to alumina was found to be 92. The Bronsted acid site density determined by temperature-programmed desorption of n-propylamine was found to be 248 μmol H + / g.
[0138] Analysis of the nitrogen and argon isotherms and the PSD calculated from the isotherms showed that the material showed only small changes in micropore volume and surface area, but a significant increase in total pore volume, indicating the formation of mesopores. This is consistent with the nitrogen and argon PSD, indicating the presence of mesopores.
[0139] Following the procedure in Example 1, the palladium exchanged material contained 0.5 wt% Pd.
[0140] Example 5
[0141] The 0.3 M NaOH solution was heated to 50° C., then 10 g of SSZ-91 from Example 3 (50 mL / g-zeolite) was added and stirred at 50° C. for 60 min. The solid was collected by filtration and washed thoroughly with DI water to a conductivity of less than 50 μS / cm, then dried in air at 95° C. The material was then converted to the ammonium form following the procedure given in Example 1.
[0142] The yield based on the recovered solids was 45%. Analysis of the nitrogen isotherm showed a t-map micropore volume of 0.071 cc / g and a t-map external surface area of 176 m 2 / g, and a BET surface area of 333m 2 / g. The total pore volume was measured at P / P0 = 0.95, and the measured value was 0.61cc / g. The mesopore diameter determined by PSD was calculated as The molar ratio of silica to alumina was found to be 68. The Bronsted acid site density, determined by temperature-programmed desorption of n-propylamine, was found to be 284 μmol H + / g.
[0143] The nitrogen isotherm is shown in Figure 3 The PSD calculated from the nitrogen isotherm is shown in Figure 4 The material shows only small changes in micropore volume and surface area, but a significant increase in total pore volume, indicating the formation of mesopores. This is consistent with the nitrogen and argon PSDs, which indicate the presence of mesopores.
[0144] Following the procedure in Example 1, the palladium exchanged material contained 0.5 wt% Pd.
[0145] Example 6
[0146] A solution of equal parts 0.1 M NaOH and 0.1 M tetrabutylammonium hydroxide (total hydroxide concentration 0.1 M) was prepared and heated to 50° C. Then 10 g of SSZ-91 from Example 3 (50 mL / g-zeolite) was added and the solution was stirred at 50° C. for 60 minutes. The solid was collected by filtration and washed thoroughly with DI water to a conductivity of less than 50 μS / cm and then dried in air at 95° C. The material was then converted to the ammonium form following the procedure given in Example 1.
[0147] The yield based on the recovered solids was 77%. Analysis of the nitrogen isotherm showed a t-map micropore volume of 0.082 cc / g and a t-map external surface area of 196 m 2 / g, and a BET surface area of 379m 2 / g. The total pore volume was measured at P / P0 = 0.95 and was found to be 0.46 cc / g. The molar ratio of silica to alumina was found to be 97. The Bronsted acid site density determined by temperature-programmed desorption of n-propylamine was found to be 242 μmol H + / g.
[0148] Analysis of the nitrogen and argon isotherms and the PSD calculated from the isotherms showed that the material showed only small changes in micropore volume and surface area, but a significant increase in total pore volume, indicating the formation of mesopores. This is consistent with the nitrogen and argon PSD, indicating the presence of mesopores.
[0149] Following the procedure in Example 1, the palladium exchanged material contained 0.5 wt% Pd.
[0150] Example 7
[0151] A sample of as-made zeolite SSZ-91 was prepared according to U.S. Patent No. 9,802,830. The material was calcined in air by placing a thin bed in a calcining dish and heating in a muffle furnace from room temperature to 120°C at a rate of 1°C / min and holding for 2 hours. The temperature was raised to 540°C at a rate of 1°C / min and held for 5 hours. The temperature was again raised to 595°C at 1°C / min and held for 5 hours. The material was then cooled to room temperature. The material was not ammonium exchanged.
[0152] For analytical purposes, a small amount of material was converted to the ammonium form following the procedure given in Example 1. Analysis of the nitrogen isotherm showed a t-map micropore volume of 0.082 cc / g and a t-map external surface area of 85 m 2 / g, and a BET surface area of 263 m 2 The total pore volume was measured at P / P0=0.95 and the found value was 0.25 cc / g. The found value of the silica to alumina molar ratio was 119.
[0153] Example 8
[0154] A 0.1 M NaOH solution was heated to 50°C, then 50 g of SSZ-91 from Example 7 (10 mL / g-zeolite) was added and stirred at 50°C for 60 min. At the end of the treatment, ice was added to quickly cool the solution. The solid was collected by filtration and washed thoroughly with DI water to a conductivity of less than 50 μS / cm, then dried at 95°C in air. The material was then converted to the ammonium form following the procedure given in Example 1.
[0155] The yield based on the recovered solids was 73%. Analysis of the nitrogen isotherm showed a t-map micropore volume of 0.052 cc / g and a t-map external surface area of 98 m 2 / g, and a BET surface area of 213 m 2 / g. The total pore volume was measured at P / P0 = 0.95, and the measured value was 0.26 cc / g. The Bronsted acid site density determined by programmed temperature desorption of n-propylamine was 198 μmol H + / g.
[0156] Analysis of the nitrogen isotherms and the PSD calculated from the isotherms show that the material shows only small changes in micropore volume and surface area without a large increase in total pore volume, indicating limited mesopore formation. This is consistent with the nitrogen PSD.
[0157] Following the procedure in Example 1, the palladium exchanged material contained 0.5 wt% Pd.
[0158] Example 9
[0159] A 0.1 M NaOH solution was heated to 50°C, then 10 g of the original synthesized SSZ-91 from Example 7 (50 mL / g-zeolite) was added and stirred at 50°C for 60 min. At the end of the treatment, ice was added to quickly cool the solution. The solid was collected by centrifugation and washed thoroughly with DI, then dried at 95°C in air. The material was then converted to the ammonium form following the procedure given in Example 1.
[0160] The yield based on recovered solids was 73%. Analysis of the nitrogen isotherm showed a t-map micropore volume of 0.071 cc / g and a t-map external surface area of 125 m 2 / g, and a BET surface area of 293m 2 / g. The total pore volume was measured at P / P0 = 0.95, and the measured value was 0.29cc / g. The mesopore diameter determined by PSD was calculated as The Bronsted acid site density was determined by temperature-programmed desorption of n-propylamine and was found to be 231 μmol H + / g.
[0161] Following the procedure in Example 1, the palladium exchanged material contained 0.5 wt% Pd.
[0162] Example 10
[0163] A 0.1 M NaOH solution was heated to 50° C., then 10 g of SSZ-91 (50 mL / g-zeolite) from Example 3 was added and stirred at 50° C. for 60 min. Ice was added to quickly cool the solution, and the solids were collected by filtration and washed thoroughly with DI water to a conductivity of less than 50 μS / cm, then dried in air at 95° C. The material was then converted to the ammonium form following the procedure given in Example 1.
[0164] The yield based on the recovered solids was 69%. Analysis of the nitrogen isotherm showed a t-map micropore volume of 0.061 cc / g and a t-map external surface area of 184 m 2 / g, and a BET surface area of 321m 2 / g. The total pore volume was measured at P / P0 = 0.95, and the measured value was 0.47cc / g. The mesopore diameter determined by PSD was calculated as The molar ratio of silica to alumina was found to be 80. The Bronsted acid site density was found to be 228 μmol H by temperature-programmed desorption of n-propylamine. + / g.
[0165] Analysis of the nitrogen isotherms and the PSD calculated from the isotherms showed that the material showed only small changes in micropore volume and surface area, but a significant increase in total pore volume, indicating the formation of mesopores. This is consistent with the nitrogen PSD, which indicates the presence of mesopores.
[0166] Following the procedure in Example 1, the palladium exchanged material contained 0.5 wt% Pd.
[0167] Embodiment 11
[0168] A 0.1 M NaOH solution was heated to 50° C., then 5 g of SSZ-91 (100 mL / g-zeolite) from Example 3 was added and stirred for 60 min at 50° C. Ice was added to quickly cool the solution, the solids were collected by filtration and washed thoroughly with DI water to a conductivity of less than 50 μS / cm, then dried in air at 95° C. The material was then converted to the ammonium form following the procedure given in Example 1.
[0169] The yield based on the recovered solids was 55%. Analysis of the nitrogen isotherm showed a t-map micropore volume of 0.071 cc / g and a t-map external surface area of 207 m 2 / g, and a BET surface area of 364m 2 / g. The total pore volume was measured at P / P0 = 0.95, and the measured value was 0.66cc / g. The mesopore diameter determined by PSD was calculated as The Bronsted acid site density was determined by temperature-programmed desorption of n-propylamine and was found to be 269 μmol H+ / g.
[0170] The nitrogen isotherm is shown in Figure 5 The PSD calculated from the nitrogen isotherm is shown in Figure 6 The material shows only small changes in micropore volume and surface area, but a significant increase in total pore volume, indicating the formation of mesopores. This is consistent with the nitrogen PSD, indicating the presence of mesopores.
[0171] Following the procedure in Example 1, the palladium exchanged material contained 0.5 wt% Pd.
[0172] Example 12
[0173] A 0.05 M NaOH solution was heated to 50° C., then 10 g of SSZ-91 (50 mL / g-zeolite) from Example 3 was added and stirred at 50° C. for 60 min. Ice was added to quickly cool the solution, the solids were collected by filtration and washed thoroughly with DI water to a conductivity of less than 50 μS / cm, then dried in air at 95° C. The material was then converted to the ammonium form following the procedure given in Example 1.
[0174] The yield based on recovered solids was 83%. Analysis of the nitrogen isotherm showed a t-map micropore volume of 0.061 cc / g and a t-map external surface area of 143 m 2 / g, and a BET surface area of 278m 2 / g. The total pore volume was measured at P / P0 = 0.95, and the measured value was 0.33cc / g. The mesopore diameter determined by PSD was calculated as The Bronsted acid site density was determined by temperature-programmed desorption of n-propylamine and was found to be 231 μmol H + / g.
[0175] Analysis of the nitrogen isotherms and the PSD calculated from the isotherms showed that the material showed only small changes in micropore volume and surface area, but a significant increase in total pore volume, indicating the formation of mesopores. This is consistent with the nitrogen PSD, which showed the presence of mesopores.
[0176] Following the procedure in Example 1, the palladium exchanged material contained 0.5 wt% Pd.
[0177] Embodiment 13
[0178] A 0.1 M tetrapropylammonium hydroxide solution was heated to 50° C., then 10 g of SSZ-91 (50 mL / g-zeolite) from Example 3 was added and stirred at 50° C. for 60 min. Ice was added to quickly cool the solution, and the solids were collected by filtration and washed thoroughly with DI water to a conductivity of less than 50 μS / cm, then dried in air at 95° C. The material was then converted to the ammonium form following the procedure given in Example 1.
[0179] The yield based on the recovered solids was 95%. Analysis of the nitrogen isotherm showed a t-map micropore volume of 0.062 cc / g and a t-map external surface area of 95 m 2 / g, and a BET surface area of 230 m 2 / g. The total pore volume was measured at P / P0 = 0.95, and the found value was 0.24 cc / g. The found value of the Brønsted acid site density determined by programmed temperature desorption of n-propylamine was 212 μmol H + / g.
[0180] Analysis of the nitrogen isotherms and the PSD calculated from the isotherms show that the material shows only small changes in micropore volume and surface area without a large increase in total pore volume, indicating limited mesopore formation. This is consistent with the nitrogen PSD.
[0181] Following the procedure in Example 1, the palladium exchanged material contained 0.5 wt% Pd.
[0182] Embodiment 14
[0183] A 0.1 M NaOH solution was heated to 50° C., then 10 g of SSZ-91 (50 mL / g-zeolite) from Example 7 was added and stirred at 50° C. for 30 min. Ice was added to quickly cool the solution, and the solids were collected by filtration and washed thoroughly with DI water to a conductivity of less than 50 μS / cm, then dried in air at 95° C. The material was then converted to the ammonium form following the procedure given in Example 1.
[0184] The yield based on the recovered solids was 66%. Analysis of the nitrogen isotherm showed a t-map micropore volume of 0.057 cc / g and a t-map external surface area of 186 m 2 / g, and a BET surface area of 315m 2 / g. The total pore volume was measured at P / P0 = 0.95, and the measured value was 0.51 cc / g. The mesopore diameter determined by PSD was calculated as The molar ratio of silica to alumina was found to be 81. The Bronsted acid site density was found to be 255 μmol H by temperature-programmed desorption of n-propylamine. + / g.
[0185] Analysis of the nitrogen isotherms and the PSD calculated from the isotherms showed that the material showed only small changes in micropore volume and surface area, but a significant increase in total pore volume, indicating the formation of mesopores. This is consistent with the nitrogen PSD, which showed the presence of mesopores.
[0186] Following the procedure in Example 1, the palladium exchanged material contained 0.5 wt% Pd.
[0187] Embodiment 15
[0188] A 0.1 M NaOH solution was heated to 50° C., then 10 g of SSZ-91 (50 mL / g-zeolite) from Example 7 was added and stirred at 50° C. for 120 min. Ice was added to quickly cool the solution, and the solids were collected by filtration and washed thoroughly with DI water to a conductivity of less than 50 μS / cm, then dried in air at 95° C. The material was then converted to the ammonium form following the procedure given in Example 1.
[0189] The yield based on the recovered solids was 64%. Analysis of the nitrogen isotherm showed a t-map micropore volume of 0.060 cc / g and a t-map external surface area of 168 m 2 / g, and a BET surface area of 300m 2 / g. The total pore volume was measured at P / P0 = 0.95, and the measured value was 0.49cc / g. The mesopore diameter determined by PSD was calculated as The molar ratio of silica to alumina was found to be 80. The Bronsted acid site density was found to be 248 μmol H by temperature-programmed desorption of n-propylamine. + / g.
[0190] Analysis of the nitrogen isotherms and the PSD calculated from the isotherms showed that the material showed only small changes in micropore volume and surface area, but a significant increase in total pore volume, indicating the formation of mesopores. This is consistent with the nitrogen PSD, which showed the presence of mesopores.
[0191] Following the procedure in Example 1, the palladium exchanged material contained 0.5 wt% Pd.
[0192] Example 16
[0193] 30 g of SSZ-91 (50 mL / g-zeolite) from Example 7 was added to a 0.1 M NaOH solution at ambient temperature 26°C and stirred for 60 min at a temperature of 26°C. The solid was collected by filtration and washed thoroughly with DI water to a conductivity of less than 50 μS / cm and then dried in air at 95°C. The product yield was 91% based on the solid recovered at this step. The material was then converted to the ammonium form following the procedure given in Example 1.
[0194] The yield based on recovered solids was 75%. Analysis of the nitrogen isotherm showed a t-map micropore volume of 0.055 cc / g and a t-map external surface area of 115 m 2 / g, and a BET surface area of 237 m 2 / g. The total pore volume was measured at P / P0 = 0.95 and was found to be 0.29 cc / g. The molar ratio of silica to alumina was found to be 104. The Bronsted acid site density determined by programmed temperature desorption of n-propylamine was found to be 220 μmol H + / g.
[0195] Embodiment 17
[0196] The 0.1 M NaOH solution was heated to 50°C, then 30 g of SSZ-91 (50 mL / g-zeolite) from Example 7 was added and stirred at 50°C for 30 min. The solids were collected by filtration and washed thoroughly with DI water to a conductivity of less than 50 μS / cm, then dried in air at 95°C. The product yield was 73% based on the solids recovered at this step. The material was then converted to the ammonium form following the procedure given in Example 1.
[0197] The yield based on the recovered solid was 65%. The nitrogen isotherm and the PSD calculated from the isotherm are shown in Figure 7 and Figure 8 The analysis of nitrogen isotherms showed that the t-diagram micropore volume was 0.058 cc / g and the t-diagram surface area was 161 m 2 / g, and a BET surface area of 289m 2 / g. The total pore volume was measured at P / P0 = 0.95, and the measured value was 0.35cc / g. The mesopore diameter determined by PSD was calculated as The molar ratio of silica to alumina was found to be 81. The Bronsted acid site density was found to be 247 μmol H by temperature-programmed desorption of n-propylamine. + / g.
[0198] Embodiment 18
[0199] A 0.1 M NaOH solution was heated to 50°C, then 30 g of SSZ-91 from Example 7 (50 mL / g-zeolite) was added and stirred at 50°C for 15 min. The solid was collected by filtration and washed thoroughly with DI water to a conductivity of less than 50 μS / cm, then dried in air at 95°C. The product yield was 76% based on the solid recovered at this step. The material was then converted to the ammonium form following the procedure given in Example 1.
[0200] The yield based on recovered solids was 68%. Analysis of the nitrogen isotherm showed a t-map micropore volume of 0.058 cc / g and a t-map external surface area of 155 m 2 / g, and a BET surface area of 285m 2 / g. The total pore volume was measured at P / P0 = 0.95, and the measured value was 0.42cc / g. The mesopore diameter determined by PSD was calculated as The molar ratio of silica to alumina was found to be 85. The Bronsted acid site density was found to be 240 μmol H by temperature-programmed desorption of n-propylamine. + / g.
[0201] Embodiment 19
[0202] A 0.05M NaOH solution was heated to 50°C, then 80 g of SSZ-91 from Example 7 (50 mL / g-zeolite) was added and stirred at 50°C for 45 min. The solid was collected by filtration and washed thoroughly with DI water to a conductivity of less than 50 μS / cm, then dried in air at 95°C. The product yield was 80% based on the solid recovered at this step. The material was then converted to the ammonium form following the procedure given in Example 1.
[0203] The yield based on recovered solids was 74%. Analysis of the nitrogen isotherm showed a t-map micropore volume of 0.063 cc / g and a t-map external surface area of 174 m 2 / g, and a BET surface area of 315m 2 / g. The total pore volume was measured at P / P0 = 0.95, and the measured value was 0.36cc / g. The mesopore diameter determined by PSD was calculated as The molar ratio of silica to alumina was found to be 93. The Bronsted acid site density, determined by temperature-programmed desorption of n-propylamine, was found to be 236 μmol H + / g.
[0204] Embodiment 20
[0205] A 0.05M NaOH solution was heated to 50°C, then 80 g of SSZ-91 from Example 7 (50 mL / g-zeolite) was added and stirred at 50°C for 60 min. The solid was collected by filtration and washed thoroughly with DI water to a conductivity of less than 50 μS / cm, then dried in air at 95°C. The product yield based on the recovered solid was 65%. The material was then converted to the ammonium form following the procedure given in Example 1.
[0206] The analysis of nitrogen isotherms showed that the micropore volume of the t-diagram method was 0.064cc / g and the surface area of the t-diagram method was 211m 2 / g, and a BET surface area of 353 m 2 / g. The total pore volume was measured at P / P0 = 0.95, and the measured value was 0.53 cc / g. The mesopore diameter determined by PSD was calculated as The molar ratio of silica to alumina was found to be 74. The Bronsted acid site density, determined by temperature-programmed desorption of n-propylamine, was found to be 269 μmol H + / g.
[0207] Example 21 - Hydroisomerization of n-hexadecane based on Example 1
[0208] 0.5 g of the palladium exchanged sample from Example 1 was added to the center of a 23 inch long x 0.25 inch outer diameter stainless steel reaction tube, and corundum was added upstream of the catalyst to preheat the feed (total pressure was 1200 psig; the downward flowing hydrogen rate was 160 mL / min (when measured at 1 atmosphere and 25°C); the downward flowing liquid feed rate was 1 mL / hour). All materials were first reduced in flowing hydrogen at about 315°C for 1 hour. The products were analyzed once every thirty minutes by online capillary gas chromatography (GC). The raw data from the GC was collected by an automatic data collection and processing system, and the hydrocarbon conversion was calculated from the raw data.
[0209] Conversion is defined as the number of products that are produced by the reaction (including iso-nC 16 The yield is higher than that of n-hexadecane except nC 16 The weight percentage of the products other than iso-C 16 The products are included as yields. The results at 96% conversion are reported in Table 5.
[0210] Example 22-40 - Hydroisomerization of n-hexadecane based on Example 2-20
[0211] Catalytic testing was performed in the same manner as Example 21 (using the material of Example 1), except that the catalyst used materials from Examples 2-20, respectively. The results at 96% conversion are reported in Table 5. The preferred materials of the present invention have an ideal isomerization selectivity of at least 87% at 96% conversion. A good balance between isomerization selectivity and temperature at 96% conversion is critical to the present invention. The ideal temperature at 96% conversion is below 600°F.
[0212] The lower the temperature at 96% conversion, the more ideal the catalyst. The best catalytic performance depends on the synergy between isomerization selectivity and temperature at 96% conversion. 4-The cracking level shows undesirable catalytic cracking and the accompanying high gas production. The ideal C of the material of the present invention 4- Cracking is less than 1.0%, or less than 0.9%.
[0213] Table 5 Summary of n-hexadecane hydrogenation conversion at 96% conversion
[0214]
[0215] It will be understood that the present invention is not limited to the above-described embodiments, and that various modifications and improvements may be made without departing from the concepts described herein. Unless mutually exclusive, any feature may be used alone or in combination with any other feature, and the present disclosure extends to and includes all combinations and sub-combinations of one or more features described herein.
[0216] Additional details regarding the invention and the scope of the disclosure may be determined from the appended claims.
[0217] The foregoing description of one or more embodiments of the invention is primarily for purposes of illustration, and it should be recognized that variations may be used that still incorporate the essence of the invention. In determining the scope of the invention, reference should be made to the appended claims.
[0218] For purposes of U.S. patent practice, and in other patent offices where permitted, all patents and publications cited in the foregoing description of the invention are incorporated herein by reference to the extent any information they contain is consistent with and / or supplementary to the foregoing disclosure.
Claims
1. A medium-pore molecular sieve belonging to the ZSM-48 zeolite family, wherein the molecular sieve comprises: A silicon oxide to aluminum oxide molar ratio of 40 to 220, at least 70% of the total ZSM-48-type material present in the molecular sieve is polytype 6, and an additional EUO-type molecular sieve phase in an amount of 0 to 3.5 wt % of the molecular sieve; wherein the molecular sieve has a morphology characterized as comprising polycrystalline aggregates of crystallites collectively having an average aspect ratio of about 1 to 8; and The molecular sieve has a total pore volume of at least about 0.2 cc / g and a micropore volume of at least 0.05 cc / g in the mesopore diameter range when P / P0 is 0.
95.
2. A medium-porous SSZ-91 molecular sieve according to claim 1.
3. A mesoporous SSZ-91 molecular sieve having a total pore volume of at least about 0.2 cc / g and a micropore volume of at least 0.05 cc / g within the mesopore diameter range when P / P0 is 0.
95.
4. The molecular sieve according to any one of claims 1 to 3, wherein the molecular sieve has a total pore volume of at least about 0.25 cc / g, or in the range of about 0.25 to 0.8 cc / g, or in the range of about 0.28 to 0.65 cc / g, or in the range of about 0.28 to 0.60 cc / g when P / P0 is 0.
95.
5. The molecular sieve according to any one of claims 1 to 4, wherein the molecular sieve has a total pore volume of at least about 0.2 to 0.6 cc / g, or about 0.22 to 0.55 cc / g, or about 0.22 to 0.0.50 cc / g in the mesopore diameter range when P / P0 is 0.
95.
6. The molecular sieve according to any one of claims 1 to 5, wherein the molecular sieve has a micropore volume in the range of about 0.05 to 0.100 cc / g, or in the range of about 0.05 to 0.090 cc / g, or in the range of about 0.05 to 0.085 cc / g.
7. The molecular sieve according to any one of claims 1 to 6, wherein the molecular sieve has a molecular weight of at least about 275 m 2 / g, or about 275 to 500m 2 / g, or in the range of about 275 to 450 m 2 / g, or about 275 to 400 m 2 The BET surface area is in the range of 1000 Å / g.
8. The molecular sieve of any one of claims 1 to 7, wherein the molecular sieve has a Bronsted acidity of at least about 175 mmol / g, or in the range of about 175 to 500 mmol / g, or in the range of about 175 to 400 mmol / g, or in the range of about 175 to 300 mmol / g.
9. The molecular sieve of any one of claims 1 to 8, wherein the molecular sieve has a silica to alumina ratio (SAR) in the range of about 40-200, or in the range of about 40-150, or in the range of about 40-120.
10. A method for preparing a mesoporous molecular sieve belonging to the ZSM-48 zeolite family, the molecular sieve having a total pore volume of at least about 0.2 cc / g and a micropore volume of at least 0.05 cc / g in the mesopore diameter range at a P / P0 of 0.95, the method comprising: preparing a reaction mixture comprising at least one silicon source, at least one aluminum source, at least one source of an element selected from Group 1 and Group 2 of the Periodic Table of Elements, hydroxide ions, hexamethylammonium cations, and water; subjecting the reaction mixture to crystallization conditions sufficient to form crystals of the molecular sieve; subjecting the molecular sieve to calcination conditions sufficient to form a calcined molecular sieve; contacting the calcined molecular sieve with an organic base, a quaternary ammonium salt, a quaternary ammonium base, an inorganic base, ammonium fluoride, or a combination thereof under solution conditions effective to desiliconize the molecular sieve; and The desiliconized molecular sieve is contacted with an ammonium salt under solution conditions effective to form an ammonium-exchanged mesoporous molecular sieve.
11. The method of claim 10, wherein the calcination conditions comprise heating the molecular sieve to a temperature in the range of 80 to 140°C for a period of 60 to 200 min; heating the molecular sieve to a temperature in the range of 450 to 550°C for a period of 60 to 300 min; heating the molecular sieve to a temperature in the range of 560 to 600°C for a period of 60 to 300 min; or a combination thereof.
12. The method of claim 11, wherein the calcination conditions include heating the molecular sieve to a temperature in the range of 80 to 140°C for a period of 60 to 200 min; heating the molecular sieve to a temperature in the range of 450 to 550°C for a period of 60 to 300 min; and heating the molecular sieve to a temperature in the range of 560 to 600°C for a period of 60 to 300 min.
13. The method of claim 10, wherein the mesoporous molecular sieve is SSZ-91.
14. The method of claim 10, wherein the ammonium salt contacted with the desiliconized molecular sieve comprises ammonium halide, ammonium chloride, ammonium acetate, ammonium nitrate or ammonium sulfate.
15. A method for preparing a mesoporous SSZ-91 molecular sieve having a total pore volume in the mesopore diameter range of at least about 0.2 cc / g (measured at P / P0 of 0.95), the method comprising: contacting the calcined SSZ-91 molecular sieve with an organic base, a quaternary ammonium salt, a quaternary ammonium base, an inorganic base, ammonium fluoride, or a combination thereof under solution conditions effective to desiliconize the molecular sieve; and The desiliconized molecular sieve is contacted with an ammonium salt under solution conditions effective to form an ammonium-exchanged mesoporous molecular sieve.
16. The method of claim 15, wherein the calcined SSZ-91 calcination conditions comprise heating the molecular sieve to a temperature in the range of 80 to 140°C for a period of 60 to 200 min; and a) heating the molecular sieve to a temperature in the range of 450 to 550°C for a period of 60 to 300 min; or b) heating the molecular sieve to a temperature in the range of 560 to 600°C for a period of 60 to 300 min; or a combination thereof.
17. The method of claim 15, wherein the calcined SSZ-91 calcination conditions include heating the molecular sieve to a temperature in the range of 80 to 140°C for a period of 60 to 200 min; heating the molecular sieve to a temperature in the range of 450 to 550°C for a period of 60 to 300 min; and heating the molecular sieve to a temperature in the range of 560 to 600°C for a period of 60 to 300 min.
18. The method according to any one of claims 10 to 17, wherein the concentration of the inorganic base is in the range of 0.001-5 mol / L, or in the range of 0.01-2 mol / L, or in the range of 0.02-1.0 mol / L.
19. The process of any one of claims 10 to 17, wherein the concentration of the ammonium salt contacted with the desiliconized molecular sieve is in the range of 0.01-80 wt%, or in the range of 1-60 wt%, or in the range of 10-50 wt%.
20. The method of any one of claims 10 to 18, wherein the ratio of molecular sieve to solution (wt / wt) is in the range of 0.001-1.0, or in the range of 0.005-0.2, or in the range of 0.01-0.
1.
21. The method according to any one of claims 10 to 19, wherein the hydroxide (OH) provided by the inorganic base - ) to the molecular sieve in a ratio of 2.5x10 -4 Up to 1.0x10 -2 mol OH - / g-molecular sieve, or within the range of 2.5x10 -4 Up to 5.0x10 -3 mol OH - / g-molecular sieve, or within the range of 2.5x10 -4 Up to 3.0x10 -3 mol OH - / g-molecular sieve range.
22. A method according to any one of claims 10 to 20, wherein the solution temperature is in the range of 1-95°C, or in the range of 5-95°C, or in the range of ambient temperature to 95°C, or wherein the solution temperature is up to the boiling point of the solution.
23. A method according to any one of claims 10 to 21 wherein the desilication temperature is in the range of 1-95°C, or in the range of 5-95°C, or in the range of ambient temperature to 95°C.
24. The method of any one of claims 10 to 22, wherein the method comprises agitating the solution by stirring, tumbling, ultrasound or a combination thereof.
25. The method of any one of claims 10 to 23, wherein the method comprises separating the molecular sieve from the solution by filtration, centrifugation, sedimentation, or a combination thereof.
26. A catalyst comprising the molecular sieve according to any one of claims 1 to 9 and a metal selected from metals of Groups 7 to 10 and 14 of the Periodic Table of Elements.
27. The catalyst of claim 26, wherein the metal comprises Pt, Pd, or a combination thereof.
28. A method for preparing a catalyst according to claim 26 or claim 27, wherein the molecular sieve is prepared according to the method of any one of claims 10 to 25.
29. A hydroconversion process for hydroisomerizing a hydrocarbon feedstock, the process comprising contacting a hydrocarbon feedstock with a hydroisomerization catalyst under hydroisomerization conditions to produce a product; in, The hydroisomerization catalyst comprises a medium pore molecular sieve belonging to the ZSM-48 zeolite family, the molecular sieve having a total pore volume of at least about 0.2 cc / g and a micropore volume of at least 0.05 cc / g in the medium pore diameter range at a P / P0 of 0.95; and Wherein, the molecular sieve comprises: A silicon oxide to aluminum oxide molar ratio of 40 to 220, at least 70% of the total ZSM-48-type material present in the molecular sieve is polytype 6, and an additional EUO-type molecular sieve phase in an amount of 0 to 3.5 wt % of the total product; wherein the molecular sieve has a morphology characterized by comprising polycrystalline aggregates of crystallites collectively having an average aspect ratio of about 1 to about 8.
30. The process of claim 29, wherein the molecular sieve is SSZ-91.
31. A hydroconversion process useful for hydroisomerizing a hydrocarbon feedstock, the process comprising: contacting a hydrocarbon feedstock with a hydroisomerization catalyst under hydroisomerization conditions to produce a product; The hydroisomerization catalyst comprises a medium pore SSZ-91 molecular sieve having a total pore volume of at least about 0.2 cc / g in the medium pore diameter range (measured at P / P0 of 0.95), and a micropore volume of at least 0.05 cc / g.
32. A process according to any one of claims 29 to 31 wherein the catalyst comprises a metal selected from Group 7 to Group 10 and Group 14 metals of the Periodic Table of Elements.
33. The method of any one of claims 29 to 32, wherein the catalyst comprises Pt, Pd, or a combination thereof.
34. The method of any one of claims 29 to 33, wherein the molecular sieve comprises: at least 80% or 90% of the total ZSM-48 type material polytype 6; 0.1 to 2 wt% EU-1; crystallites having an average aspect ratio of 1 to 5 or 1 to 3; or a combination thereof.
35. A process according to any one of claims 29 to 34 wherein the catalyst metal content is 0.01-5.0 wt% or 0.01-2.0 wt% or 0.1-2.0 wt% (based on total catalyst weight).
36. The method of any one of claims 29 to 35, wherein the molecular sieve has a silica to alumina molar ratio (SAR) in the range of about 40-200, or in the range of about 40-150, or in the range of about 40-120, or in the range of about 50-200, or in the range of about 50-150, or in the range of about 50-120.
37. The method of any one of claims 29 to 36, wherein the catalyst further comprises a matrix material selected from alumina, silica, titania, or a combination thereof.
38. The method of claim 37, wherein the catalyst comprises 0.01 to 5.0 wt% of the metal, 1 to 80 wt% of the matrix material, and 0.1 to 99 wt% of the molecular sieve.
39. The process of any one of claims 29 to 38, wherein the hydrocarbon feed comprises gas oil; vacuum gas oil; long boiling residue; vacuum residue; atmospheric distillates; heavy fuels; oils; waxes and paraffins; used oils; deasphalted residues or crude oils; charges resulting from thermal or catalytic conversion processes; shale oils; cycle oils; fats, oils and waxes of animal and vegetable origin; petroleum and slack waxes; or combinations thereof.
40. A method for producing a hydroisomerized hydrocarbon product having an isomerization selectivity of 90% or more (at 96% nC 16 conversion rate), 585℉ or lower catalyst activity temperature (at 96% nC 16 conversion rate) or 0.9% or less as the generated C 4- The method comprises subjecting a hydrocarbon feed to a method according to any one of claims 30 to 40.
41. The method of claim 40, wherein the selectivity is 90% or more and the catalyst activity temperature is 585°F or less, or the selectivity is 90% or more and as the produced C 4- The light fraction yield measured as cracked product is 0.9% or less, or the catalyst activity temperature is 585°F or less and as the produced C 4- The light fraction yield measured as cracked products is 0.9% or less, or a combination thereof.
42. The method of claim 40, wherein the selectivity is 90% or more, the catalyst activity temperature is 585°F or less, and as produced C 4- The light fraction yield measured as cracked products is 0.9% or less.
43. The process of any one of claims 41 or 42, wherein the selectivity is equal to or greater than 91% or 92%, or wherein the catalyst activity temperature is equal to or less than 582°F, or 580°F, or 575°F, or 570°F, or wherein C 4- The light fraction yield of cracked products is equal to or less than 0.85%, or 0.8%, or 0.7%, or 0.6%, or 0.5%, or 0.4%, or 0.3%, or 0.2%, or a combination thereof.
44. A hydroconversion catalyst for use in the process of any one of claims 29 to 40, the catalyst comprising a medium pore molecular sieve belonging to the ZSM-48 zeolite family, the molecular sieve having a pore volume of at least about 0.2 cc / g and a micropore volume of at least 0.05 cc / g in the mesopore diameter range at a P / P0 of 0.95; and wherein, The molecular sieve comprises: A silicon oxide to aluminum oxide molar ratio of 40 to 220, at least 70% of the total ZSM-48-type material present in the molecular sieve is polytype 6, and Additional EUO type molecular sieve phase in an amount of 0 to 3.5 wt % of the total molecular sieve; wherein the molecular sieve has a morphology characterized by comprising polycrystalline aggregates of crystallites collectively having an average aspect ratio of about 1 to about 8.
45. The catalyst of claim 44, wherein the molecular sieve is SSZ-91.
46. A hydroconversion catalyst for use in the process of any one of claims 30 to 41, the catalyst comprising a medium pore SSZ-91 molecular sieve having a total pore volume in the medium pore diameter range of at least about 0.2 cc / g (measured at P / P0 of 0.95), and wherein the micropore volume is at least 0.05 cc / g.
47. The catalyst of any one of claims 44 to 46, wherein the metal comprises Pt, Pd, or a combination thereof.
48. A method for preparing a catalyst according to any one of claims 44 to 46, wherein the molecular sieve is prepared according to the method according to any one of claims 10 to 25.
49. The method of claim 48, wherein the molecular sieve is prepared by a method comprising the steps of Preparing a reaction mixture comprising at least one silicon source, at least one aluminum source, at least one source of an element selected from Group 1 and Group 2 of the Periodic Table of Elements, hydroxide ions, hexamethylammonium cations, and water; and subjecting the reaction mixture to crystallization conditions sufficient to form crystals of the molecular sieve; subjecting the molecular sieve to calcination conditions sufficient to form a calcined molecular sieve; contacting the calcined molecular sieve with an organic base, a quaternary ammonium salt, a quaternary ammonium base, an inorganic base, ammonium fluoride, or a combination thereof under solution conditions effective to desiliconize the molecular sieve; and The desiliconized molecular sieve is contacted with an ammonium salt under solution conditions effective to form an ammonium-exchanged mesoporous molecular sieve.
Citation Information
Patent Citations
Catalysts and method of their preparation
US4094821A
Zeolite SSZ-26
US4910006A
Zeolite SSZ-35
US5316753A
Methods to improve heteroatom lattice substitution in large and extra-large pore borosilicate zeolites
US6790433B2
Methods for removing organic compounds from nano-composite materials
US6960327B2